Promoting the uptake of HIV testing among men who have sex with men: systematic review of effectiveness and cost-effectiveness. Issue 4 (25th March 2011) - Lorenc, Theo; Marrero-Guillamón, Isaac; Aggleton, Peter; Cooper, Chris; Llewellyn, Alexis; Lehmann, Angela; Lindsay, Catriona
Abstract : What interventions are effective and cost-effective in increasing the uptake of HIV testing among men who have sex with men (MSM)? A systematic review was conducted of the following databases: AEGIS, ASSIA, BL Direct, BNI, Centre for Reviews and Dissemination, Cochrane Database of Systematic Reviews, CINAHL, Current Contents Connect, EconLit, EMBASE, ERIC, HMIC, Medline, Medline In-Process, NRR, PsychINFO, Scopus, SIGLE, Social Policy and Practice, Web of Science, websites, journal hand-searching, citation chasing and expert recommendations. Prospective studies of the effectiveness or cost-effectiveness of interventions (randomised controlled trial (RCT), controlled trial, one-group or any economic analysis) were included if the intervention aimed to increase the uptake of HIV testing among MSM in a high-income (Organization for Economic Co-operation and Development) country. Quality was assessed and data were extracted using standardised tools. Results were synthesised narratively. Twelve effectiveness studies and one cost-effectiveness study were located, covering a range of intervention types. There is evidence that rapid testing and counselling in community settings (one RCT), and intensive peer counselling (one RCT), can increase the uptake of HIV testing among MSM. There are promising results regarding the introduction of opt-out testing in sexually transmitted infection clinics (two one-group studies). Findings regarding other interventions, including bundling HIV tests with other tests, peer outreach in community settings, and media campaigns, are inconclusive. Findings indicate several promising approaches to increasing HIV testing among MSM. However, there is limited evidence overall, and evidence for the effectiveness of key intervention types (particularly peer outreach and media campaigns) remains lacking.